Solitary Plasmacytoma of bilateral temporal bone in a patient with multiple myeloma - Nouf Albakheet; Elaf Essa Ahmed; Yazeed Al-Shawi; Khabti Almuhanna (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Introduction: Plasmacytomas are tumors that results from monoclonal proliferation of plasma cells. Disseminated form is called Multiple Myeloma (MM) which is characterized by multiple lytic bone lesions on imaging and monoclonal gammopathy. Case presentation: A 53-year-old male presented to the emergency department with post auricular swelling in the right side. Thorough history and examination of the patient were done. Laboratory investigations, bone biopsy, and imaging of the patient were all consistent with MM and Solitary Plasmacytoma of Bone (SPB). The patient was started on chemotherapy and showed regression of the swelling.